Association of interleukin-10 polymorphisms with schizophrenia: a meta-analysis. - Lei Gao (Public Library of Science (PLoS), 2014)
Background The involvement of cytokines in schizophrenia (SZ) has been proposed in recent years and various studies have accumulated convergent lines of evidence. Among which, the role of interleukin-10 (IL-10) in SZ has been explored in a number of studies by investigating association of single nucleotide polymorphisms (SNPs) and susceptibility of SZ. However, the results are inconsistent since its power is limited by the individual sample size. To evaluate the overall effect between them, we conducted a meta-analysis by combining all available studies. Methods Studies were searched from the database of PubMed, PsycINFO and ISI web of Knowledge up to Nov 2013. The meta-analysis was conducted based on statement of preferred reporting items for systematic reviews and meta-analyses (PRISMA). Results Eleven studies including 6399 subjects (3129 cases and 3270 controls) were available for the meta-analysis. Among three investigated SNPs, rs1800872 was observed to be significantly associated with risk of SZ (AA vs. AC+CC, Pooled OR = 1.351, P-value  = 2.06E-04). Meanwhile, among six haplotypes of rs1800896 - rs1800871 - rs1800872, significant associations were observed in haplotype A-C-A (Pooled OR = 1.762, P-value  = 2.00E-03) and G-C-C (Pooled OR = 0.649, P-value  = 2.00E-03) for Asians. These results were still significant after adjusting for multiple comparisons. Conclusions This meta-analysis demonstrated an SNP and two haplotypes of IL-10 significantly associated with SZ, suggesting that IL-10 might be a risk factor of SZ.